MEMBANGUN DAN MEMELIHARA KOMUNIKASI DALAM KONSELING - Ekawati S. Rukmana (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACTCommunication in daily life is a routine activity carried out by social creatures. Success in building good communication is determined by components effectively, empathy, and good manners between fellow educators, education staff, parents, students, and people. This study aims to find out how to create a communication relationship in counseling between BK teachers and students at Muhammadiyah Senior High School 1 of Yogyakarta. The author uses several methods to collect data, such as interviews and observations. The results of this study explain that the communication process in counseling between BK teachers and students includes several stages, namely: The first start by collecting data about students through a questionnaire tool to several problems and a list of problem notes, the second was the teacher provides opportunities for students to convey the problem they face, the third was empathize with students with verbal and non-verbal language, and the fourth was mentoring continuously to optimize students potential (every student who is naughty or problematic must have a positive side). Establishing and maintaining communication requires the following steps, these are relationship building, problem identification and assessment, facilitating counseling change, and evaluation and termination.Keywords: Communication, Counseling.Â ABSTRAKKomunikasi dalam kehidupan sehari-hari merupakan aktivitas rutin yang dilakukan oleh setiap makhluk sosial. Keberhasilan dalam membangun komunikasi yang baik sangat ditentukan oleh seluruh komponen secara efektif, empati, dan santun, baik antara sesama pendidik, tenaga kependidikan, orang tua, siswa dan masyarakat. Tujuan penelitian ini adalah untuk mengetahui bagaimana konsep membangun hubungan komunikasi dalam konseling antara guru BK dan peserta didik di sekolah SMA Muhammadiyah 1 Yogyakarta. Penulis menggunakan beberapa metode dalam pengumpulan data diantaranya wawancara dan observasi. Hasil penelitian ini menjelaskan bahwa proses komunikasi dalam konseling antara guru BK dan siswa meliputi beberapa tahapan yaitu: 1). Diawali dengan mengumpulkan data-data tentang siswa melalui kuisioner alat ungkap masalah dan daftar catatan masalah, 2). Guru memberikan kesempatan kepada siswa untuk menyampaikan masalah yang dihadapi, 3). Berempati kepada siswa dengan bahasa verbal dan non verbal, 4). Pendampingan secara terus-menerus untuk mengoptimalkan potensi siswa (setiap siswa yang nakal atau bermasalah pasti ada sisi positifnya). Membangun dan memelihara komunikasi diperlukan langkah-langkah sebagai berikut: membangun hubungan, identifikasi dan penilaian masalah, memfasilitasi perubahan konseling, serta evaluasi dan terminasi.Kata Kunci: Komunikasi, Konseling.